Uwagi o rozkładach inflacyjnych - Gerstenkorn, Tadeusz (Remarks on the Inflated Distributions, 2007)
This is a review paper on inflated distributions. Relations between moments of ordinary and inflated Pólya distributions are particularly discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 83-88